Akibat Hukum dari Perbuatan Melawan Hukum terhadap Bank dalam Transaksi Letter of Credit - Manga, Angel Fransisca Christy; Dianti, Flora (CV. Social Politic Genius (SIGn), 2023)
This study aims to understand and examine the legal consequences of unlawful acts against banks involved in L/C transactions. This study uses a normative legal research method. The collected legal material is then qualitatively analyzed to describe the problem and answer the study objectives. The results show that Board Member Regulation Number 23/21/PADG/2021 demonstrates Indonesia’s legal adaptation to UCP 600 as the international standard in L/C transactions. UCP 600 emphasizes the principle of independence about the Bank’s role, which is limited to verifying L/C transaction documents. However, there is a risk of L/C Fraud, where the Issuing Bank has the right not to pay the Exporter if there are indications of fraud, by implementing the “Fraud Rule.” The approach to L/C Fraud varies across jurisdictions; in countries with civil law systems, such actions are often considered unlawful acts, while in countries like the United States, they are viewed as criminal acts. Therefore, it is recommended that relevant stakeholders enhance their understanding and compliance with UCP 600. Issuing Banks and Advising Banks need to develop more effective mechanisms for detecting and preventing L/C Fraud, considering the different legal approaches to L/C Fraud in various jurisdictions. Training staff on the nuances of L/C Fraud and how to identify it is also essential. Furthermore, resolving L/C disputes through civil law channels is considered more appropriate, given these transactions’ commercial and contractual nature. Stakeholders should collaborate to strengthen the legal framework and procedures that support the integrity and security of L/C transactions and to align practices with international standards to enhance trust and security in international trade.